Does size matter? Center-specific characteristics and survival after allogeneic hematopoietic cell transplantation for acute myeloid leukemia: an analysis of the German Registry for Stem Cell Transplantation and Cell Therapy - Wolfgang Bethge; Sarah Flossdorf; Franziska Hanke; Christoph Schmid; Mark Ringhoffer; Stefan Klein; Bernd Hertenstein; Johannes Schetelig; Matthias Stelljes; Thomas Schroeder; Igor Wolfgang Blau; Francis Ayuk; et al. (Haematologica)
We investigated the effect of center-specific variables on overall survival (OS) after allogeneic hematopoietic cell transplantation (alloHCT) in acute myeloid leukemia (AML). Eligible were adult patients reported to DRST registry receiving first alloHCT for AML from a related or matched (>= 9/10 HLA-match) unrelated donor 2015-2021. Primary endpoint was OS at 12 months from alloHCT. Univariable and multivariable analyses after best subset selection was performed. Of 5328 patients, 83% received alloHCT in a high-volume center (≥40 alloHCT/year); 90% in a university hospital; 90% in a center performing alloHCT for ≥10 years; and 73% in a Joint Accreditation Committee IHCT-Europe and EBMT (JACIE) accredited center. 52% of the patients were in CR1, and ELN risk was adverse in 37% and intermediate in 42%. On multivariable analysis, center-specific factors predicting adverse 12-month OS were program duration